ON SOME PROPERTIES OF THE ASPECTUAL PROJECTION AND VERBAL MOVEMENT IN RUSSIAN AND LITHUANIAN - Korostenskienė, Julija (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*288.79px); top: calc(var(–scale-factor)*75.38px); font-size: calc(var(–scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.15683);" role="presentation">http://dx.doi.org/10.7220/2335-2027.8.5 Set within the generative syntactic framework, the present study explores the aspectual projection in Russian and Lithuanian. As is known, aspect is traditionally regarded to be a grammatical category in Russian, whereas there is no unanimous view on Lithuanian aspect and the latter is perceived within the lexical or lexico-grammatical range. Given the fact that both Lithuanian and Russian exhibit the features of languages with the verb merged low on the syntactic tree, while their general morphosyntactic properties are similar in many respects, e.g., rich verb morphology, tense and agreement systems, the verb may be derived by both prefixation and suffixation. Different aspectual properties present an interesting puzzle. The article aims to provide a formal account for this phenomenon. It is first shown that, similarly to Russian, the Lithuanian verb is positioned low, which is reflected in the regular appearance following manner adverbs. However, due to the varying feature strength of the relevant functional projections in each language, verbal movement in each language is realised differently, which consequently affects the morphemic layout as well as has implications for the aspect-tense correlation in each language.